2007
DOI: 10.1007/s11064-007-9437-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Preconditioning on Mitochondrial Dysfunction and Mitochondrial P53 Translocation after Transient Global Cerebral Ischemia in Rats

Abstract: Transient global brain ischemia induces dysfunctions of mitochondria including disturbance in mitochondrial protein synthesis and inhibition of respiratory chain complexes. Due to capacity of mitochondria to release apoptogenic proteins, ischemia-induced mitochondrial dysfunction is considered to be a key event coupling cerebral blood flow arrest to neuronal cell death. Ischemic preconditioning (IPC) represents an important phenomenon of adaptation of central nervous system (CNS) to sub-lethal short-term ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…In addition, IPC had significant protective effect on ischemia-induced DNA fragmentation, as well as on number of positive Fluoro-Jade C staining cells. Thus, it indicates that IPC abolished almost completely both initiation and execution of mitochondrial apoptosis induced by global brain ischemia in vulnerable CA1 layer of rat hippocampus (Racay et al, 2007(Racay et al, , 2009b. The studies showed that ischemia induced inhibition of mitochondrial complexes I and IV, however inhibition is not accompanied by a decrease of mitochondrial Ca 2+ uptake rate apparently due to the excess capacity of the complex I and complex IV.…”
Section: Impact Of Iri and Ipc On Mitochondrial Calcium Transport P5mentioning
confidence: 81%
See 3 more Smart Citations
“…In addition, IPC had significant protective effect on ischemia-induced DNA fragmentation, as well as on number of positive Fluoro-Jade C staining cells. Thus, it indicates that IPC abolished almost completely both initiation and execution of mitochondrial apoptosis induced by global brain ischemia in vulnerable CA1 layer of rat hippocampus (Racay et al, 2007(Racay et al, , 2009b. The studies showed that ischemia induced inhibition of mitochondrial complexes I and IV, however inhibition is not accompanied by a decrease of mitochondrial Ca 2+ uptake rate apparently due to the excess capacity of the complex I and complex IV.…”
Section: Impact Of Iri and Ipc On Mitochondrial Calcium Transport P5mentioning
confidence: 81%
“…Collective studies confirm, that reactive oxygen species (ROS) contribute to neuronal cell injuries secondary to ischemia and reperfusion (Lehotsky et al, 2004;Burda et al, 2005;Danielisova et al, 2005;Shi and Liu, 2007) and might initiate cell death signaling pathways after cerebral ischemia and parallels with selective post-ischemic vulnerability of the brain (Valko et al, 2007;Shi and Liu, 2007;Otani, 2008;Dirnagl et al, 2009). As shown by measurement of steady state fluorescence of ANS in hippocampal mitochondria (Racay et al, 2007(Racay et al, , 2009a, naive IRI induced significant increase in ANS flurescence (it binds to hydrophobic part of membrane lipids and proteins) of the forebrain in both ischemic and reperfusion periods. These results support data from previous experiments (Lehotsky et al, 2004;Babusikova et al, 2008), which showed that IRI induced structural changes on hippocampal membrane lipids and both, the lipoperoxidation dependent and the direct www.intechopen.com oxidative modifications of membrane proteins.…”
Section: Effect Of Oxidative Damage On Spca1mentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, it is believed that CI dysfunction and the subsequent impairment of mitochondrial respiration provoke the activation of the mitochondrial-dependent apoptotic machinery by directly triggering the release of apoptogenic molecule cytochrome c from defective mitochondria (Green and Kroemer 2004;Clayton et al 2005;Perier et al 2007). Finally, loss of mitochondrial CI catalytic activity in the electron transport chain is associated with a wide spectrum of neurodegenerative disorders (Table 1) or acute pathophysiological processes such as ischemia-reperfusion injury (Almeida et al 1995;Tompkins et al 2006;Racay et al 2007) and heart failure as well as with normal aging process (Petrosillo et al 2008). …”
Section: Introductionmentioning
confidence: 99%